The Influence of the PBL Model on Students Critical Thinking Ability in Wave Topic - Saaban, Indriani; Pikoli, Masrid; Abdjul, Tirtawaty; Mursalin, Mursalin; Yusuf, Muhammad; Nurhayati, Nurhayati (Jurnal Pijar Mipa, 2025)
The Problem-Based Learning (PBL) model is an educational innovation that improves students' thinking ability through organized team or group work. This research aims to determine the influence of the PBL model on students' critical thinking ability in wave topics. The research method used was quantitative experimental or descriptive methods. This research was carried out by collecting numerical data, which was then processed and analyzed to extract the scientific information behind it. There are two variables: X is the independent variable, and Y is the dependent variable. The sample source of the study sample was 27 students at SMP Negeri 1 Bulawa, in class VIII. The results of this research show that the calculated value of the t-test shows that the value of t-count = 57.062 at a significance level of 0.05 and t-table = 2.055. So this result shows t-count ≥ t-table. Therefore, the researcher concluded that the PBL model influenced students' critical thinking skills in wave topics.